HUBUNGAN ANTARA PENGETAHUAN DENGAN TINGKAT KECEMASAN IBU SAAT MENGHADAPI HOSPITALISASI PADA ANAK DI RUANG ANAK RSUD PAREâKEDIRI TAHUN 2008 - Lenawati, Helena; Puspitasari, Hendrit (Akademi Keperawatan Pamenang, 2010)
HospitalizationÂ ofÂ childÂ isÂ aÂ processÂ becauseÂ ofÂ aÂ reasonÂ toÂ obligateÂ aÂ childÂ toÂ stayÂ inÂ theÂ hospitalÂ thathaveÂ planningÂ orÂ emergency,Â endureÂ treatmentÂ andÂ therapyÂ untilÂ repatriatingÂ Â Â toÂ home.Â AÂ ChildÂ isÂ theÂ partÂ oftheir parent life so, if there are any experience bothering them, their parent will be worry.The objective of this research is to investigate the knowledge relation with plead of mother level in face ofhospitalizationÂ aÂ child.Â ThisÂ researchÂ isÂ useÂ analyticÂ crossÂ sectionalÂ design.Â TheÂ sampleÂ isÂ takenÂ awayÂ frommothersÂ thatÂ waitingÂ theirÂ child.Â InÂ pediatricÂ unitÂ withÂ sizeÂ sampleÂ 28Â persons,Â itÂ isÂ usingÂ purposiveÂ samplingtechnique.ResultÂ thisÂ researchÂ showÂ fromÂ 11Â responderÂ havingÂ knowledgeÂ ofÂ good,Â 7Â responderÂ havingÂ lightanxietyÂ Â levelÂ (63,6%),Â 3Â responderÂ having mediumÂ anxiety levelÂ (27,3%)Â andÂ responderÂ havingÂ heavyÂ anxietylevel (9,1%).ProgressiveyÂ goodnessÂ knowledgeÂ ofÂ mother, itÂ isÂ decreaseÂ theÂ ancietyÂ level in faceÂ ofÂ Â hospitalizationÂ achild.Â ToÂ lessenÂ theÂ anxietyÂ levelÂ ofÂ parent,Â healthyÂ officerÂ isÂ suggestedÂ toÂ giveÂ moreÂ informationÂ abouthospitalization and also medical proceeds are about treatment of a child.